Rural geography an introductory survey, - Clout, Hugh D. (Pergamon Oxford geographies., 1972)
Discusses a series of themes linked to the changing use of the rural environment in the modern world. Although the text emphasises issues in Great Britain it also compares the rural scene in France, North America, Northern Europe and Eastern Europe and has general relevance for other parts of the developed world. A special feature is the wide ranging and detailed bibliography. Suitable for students of geography, sociology, town and country planning.